Functional Biopolymers - Jafar Mazumder, Mohammad Abu; Sheardown, Heather; Al-Ahmed, Amir (Polymers and Polymeric Composites: A Reference Series, 2019)
This reference work offers a comprehensive overview of the synthesis, properties and biomedical applications of functional biopolymers. Chapters from expert contributors cover topics such as synthetic biopolymers, blood-compatible polymers, ophthalmic polymers and stimuli responsive polymers. An up-to-date review of cell encapsulation strategies and cell surface and tissue engineering is also included in this work, and readers will discover more about hydrogels and polymers from renewable resources. Edited by an international team of experts in the field, this reference work will appeal to researchers, scientists, and practitioners working in this field, or entering this vibrant research area.